The power of stories : luxury brand communication on social media - Andrade, Anna Carolina Forssblad Rebello de (2021)
The purpose of this study is to explore how luxury brands portray their values through storytelling on social media. A qualitative study was conducted due to the exploratory nature of this study using a multiple case study. Moreover, both primary and secondary data was collected. Primary data was collected through semi-structured interviews with three luxury brands and thereafter with potential consumers. The findings identified four ways luxury brands portray their values through the role of brand storytelling on social media: (1) guaranteeing consistency (2) maintaining authenticity (3) remaining aspirational (4) engaging and educating. The research adds to existing literature in the luxury sector and brand communication